2003
DOI: 10.1557/jmr.2003.0039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined metal-carbon additions on the microstructure and structure of Sm2Fe17

Abstract: The effect of combined alloying additions on the structure and scale of rapidly solidified Sm-Fe alloys was investigated. Transition metal additions tend to promote the formation of the disordered TbCu 7 -type structure in Sm 2 Fe 17 alloys, as determined by monitoring the long-range order parameter. Essentially no order was observed for M ‫ס‬ Ti, Zr, V, or Nb. Thus, the structure was close to the prototypical TbCu 7 -type structure. With M ‫ס‬ Si, a large amount of order was observed (S ‫ס‬ 0.62), resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The combined effect of the rapid solidification and alloying with Nb suppressed the formation of the Sm 2 Co 17 equilibrium structure, which requires the ordering of transition metal dumbbells. Previously, we observed that early transition metal additions inhibited the development of dumbbell ordering in Sm 2 Fe 17 alloys, leading to the formation of TbCu 7 -type structures, and, combined with C, resulted in grain refinement [14,15]. A higher resolution scan taken at long counting times between 2y ¼ 36 and 40 confirmed the lack of long-range dumbbell ordering, as shown by the absence of the (0 2 4) superstructure peak predicted at 2yB38:5 (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The combined effect of the rapid solidification and alloying with Nb suppressed the formation of the Sm 2 Co 17 equilibrium structure, which requires the ordering of transition metal dumbbells. Previously, we observed that early transition metal additions inhibited the development of dumbbell ordering in Sm 2 Fe 17 alloys, leading to the formation of TbCu 7 -type structures, and, combined with C, resulted in grain refinement [14,15]. A higher resolution scan taken at long counting times between 2y ¼ 36 and 40 confirmed the lack of long-range dumbbell ordering, as shown by the absence of the (0 2 4) superstructure peak predicted at 2yB38:5 (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Non-equilibrium processing such as rapid solidification was found to promote the formation of the TbCu 7 -type structure with disordered arrangement of dumbbell atoms in the lattice [2][3][4][5][6][7] and considerably refine the grain size [8,9]. Alloying additions of Ti and Zr were found to suppress the formation of the equilibrium 2-17 phases, leading to stabilization of the disordered TbCu 7 -type structure [3,10]; additions of Ti, V, Zr or Nb combined with C contributed to stabilization of the disordered phase and refined the grain size during melt spinning [11,12]. The formation of partially ordered Sm 2 Fe 17 with Th 2 Zn 17 -type structure was found to be independent of the wheel speed, but the alloyed compounds displayed stronger tendency to form the TbCu 7 -type structure [11].…”
Section: Introductionmentioning
confidence: 99%